2019
DOI: 10.3354/meps13073
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove lagoons of the Great Barrier Reef support coral populations persisting under extreme environmental conditions

Abstract: Acropora millepora colony thriving under extreme low pH, low oxygen and highly variable temperatures of a Great Barrier Reef mangrove lagoon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
136
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(146 citation statements)
references
References 69 publications
9
136
1
Order By: Relevance
“…Red Sea) and both acidification and warming (e.g. New Caledonia Lagoon) all their lives provide examples of acclimatization/adaptation to global change conditions (Camp et al, , , ; Fine, Gildor, & Genin, ; Foo, Byrne, Ricevuto, & Gambi, ; Hall‐Spencer et al, ; González‐Delgado & Hernández, ). These systems also incorporate environmental factors, such as nutrients, currents and species interactions, not easily replicated in the laboratory.…”
Section: Insights From Contemporary Environmental Analogues Of Globalmentioning
confidence: 99%
“…Red Sea) and both acidification and warming (e.g. New Caledonia Lagoon) all their lives provide examples of acclimatization/adaptation to global change conditions (Camp et al, , , ; Fine, Gildor, & Genin, ; Foo, Byrne, Ricevuto, & Gambi, ; Hall‐Spencer et al, ; González‐Delgado & Hernández, ). These systems also incorporate environmental factors, such as nutrients, currents and species interactions, not easily replicated in the laboratory.…”
Section: Insights From Contemporary Environmental Analogues Of Globalmentioning
confidence: 99%
“…Further, ecological surveys of Florida mangroves from the 1930s to 1980s made no mention of the presence of corals when detailing associated fauna ( Davis, 1940 ; Odum, McIvor & Smith, 1982 ). However, a number of recent studies have identified several locations around the world with corals growing on or near mangrove prop roots ( Bengtsson et al, 2019 ; Camp et al, 2019 , 2017 ; Hernández-Fernández, 2015 ; Macintyre et al, 2000 ; Rogers, 2009 , 2017 ; Scavo Lord et al, 2020 ). In some of these habitats, mangroves are sheltering corals even in the face of extreme variability in pH, dissolved oxygen, and temperature, resulting in lower incidences of bleaching and high rates of recovery ( Camp et al, 2019 , 2017 ; Yates et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mangroves are increasingly being recognized as an important component of the ecological niche for many coral species (Yates et al 2014, Hernández Fernández 2015, Rogers 2017, Bengtsson et al 2019, Camp et al 2019, Scavo Lord et al 2020. Here, we demonstrate significant differences in key environmental variables between the mangrove and adjacent coralsupporting habitats.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to directly compare the morphology of corals across mangrove and shallow patch-reef habitats. Given increasing interest in the role of non-reef habitats for supporting coral resilience (Yates et al 2014, Hernández Fernández 2015, Rogers 2017, Bengtsson et al 2019, Camp et al 2019, Scavo Lord et al 2020, it is important to understand whether and how coral phenotypes can change to accommodate the conditions found in what have historically been regarded as suboptimal habitats for corals, such as mangroves. Going forward, it will be important to differentiate genetic from environmental factors in the phenotypic diversity documented here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation